The Development of Indoor Object Recognition Tool for People with Low Vision and Blindness - Rhio Sutoyo; Andry Chowanda (ComTech: Computer, Mathematics and Engineering Applications, 2017)
The purpose of this research was to develop methods and algorithms that could be applied as the underlying base for developing an object recognition tools. The method implemented in this research was initial problem identification, methods and algorithms testing and development, image database modeling, system development, and training and testing. As a result, the system can perform with 93,46% of accuracy for indoor object recognition. Even though the system achieves relatively high accuracy in recognizing objects, it is still limited to a single object detection and not able to recognize the object in real time.